2015
DOI: 10.1371/journal.pone.0135319
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Physical Fitness in Healthy Untrained Men: Effects on VO2max, Jump Performance and Flexibility of Soccer and Moderate-Intensity Continuous Running

Abstract: The purpose of this study was to determine the effects of recreational soccer (SOC) compared to moderate-intensity continuous running (RUN) on all health-related physical fitness components in healthy untrained men. Sixty-nine participants were recruited and randomly assigned to one of three groups, of which sixty-four completed the study: a soccer training group (SOC; n = 20, 34±4 (means±SD) years, 78.1±8.3 kg, 179±4 cm); a running group (RUN; n = 21, 32±4 years, 78.0±5.5 kg, 179±7 cm); or a passive control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 42 publications
4
29
2
3
Order By: Relevance
“…18 In addition, participants in our study spent only 10% of training time above 90% HR max during football training, which is lower than that observed in other studies (~20%). [16][17][18]41 However, the stimuli elicited during the football training were sufficient for overweight and obese children to undergo similar aerobic adaptations for improved fitness to other research. 14,20 Hansen et al 21 concluded typical patterns of cardiovascular adaptations related to recreational football have similarities to interval training.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…18 In addition, participants in our study spent only 10% of training time above 90% HR max during football training, which is lower than that observed in other studies (~20%). [16][17][18]41 However, the stimuli elicited during the football training were sufficient for overweight and obese children to undergo similar aerobic adaptations for improved fitness to other research. 14,20 Hansen et al 21 concluded typical patterns of cardiovascular adaptations related to recreational football have similarities to interval training.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…Up to now, there is no question that VO 2 peak can be improved by training in healthy individuals [27]. It is unclear whether our patients with higher VO 2 peak had the habit of routine exercise in the first place.…”
Section: Discussionmentioning
confidence: 82%
“…Postoperative pathological staging yielded T1 in 186 (54.4%), T2 in 128 (37.4%), T3 in 18 (5.8%) and T4 in 7 (2%) cases. N0 was found in 191 (55,8%), N1 in 93 (27,2) and N2 in 58 (17%) patients. Union for International Cancer Control (UICC) staging revealed stage I in 182 patients (53.7 %), stage II in 85 patients (25.1 %) and stage III in 72 patients (21.2%).…”
Section: Resultsmentioning
confidence: 98%
“…Један од могућих разлога представља и начин исхране испитаника који су учествовали у експерименталном делу. Познато је да испитаници када почну са вежбањем истовремено редукују и калоријски унос (Milanović et al, 2015), међутим то се не може са сигурношћу узети као чињеница јер калоријски унос и начин исхране нису контролисани у овом истраживању. Могући разлог делимичног смањења масне компоненте код испитаника јесу веће просечне почетне вредности пре експерименталног програма што пружа могућност остварења већег ефекта за краћи временски период.…”
Section: резултатиunclassified